Mutations in the two component regulator systems PmrAB and PhoPQ give rise to increased colistin resistance in Citrobacter and Enterobacter spp. Issue 4 (3rd March 2020) - Wand, Matthew E.; Sutton, J. Mark
Abstract : Introduction. Colistin is a last resort antibiotic for treating infections caused by carbapenem-resistant isolates. Mechanisms of resistance to colistin have been widely described in Klebsiella pneumoniae and Escherichia coli but have yet to be characterized in Citrobacter and Enterobacter species. Aim. To identify the causative mutations leading to generation of colistin resistance in Citrobacter and Enterobacter spp. Methodology. Colistin resistance was generated by culturing in increasing concentrations of colistin or by direct culture in a lethal (above MIC) concentration. Whole-genome sequencing was used to identify mutations. Fitness of resistant strains was determined by changes in growth rate, and virulence in Galleria mellonella . Results. We were able to generate colistin resistance upon exposure to sub-MIC levels of colistin, in several but not all strains of Citrobacter and Enterobacter resulting in a 16-fold increase in colistin MIC values for both species. The same individual strains also developed resistance to colistin after a single exposure at 10× MIC, with a similar increase in MIC. Genetic analysis revealed that this increased resistance was attributed to mutations in PmrB for Citrobacter and PhoP in Enterobacter, although we were not able to identify causative mutations in all strains. Colistin-resistant mutants showed little difference in growth rate, and virulence in G. mellonella, although there were strain-to-strain differences. Conclusions. Stable colistin resistance may be acquired with no loss of fitness in these species. However, only select strains were able to adapt suggesting that acquisition of colistin resistance is dependent upon individual strain characteristics.